Acuity Tools for the Antepartum and Neonatal Intensive Care Units. Issue 1 (January 2023) - Roth, Cheryl; Dent, Sarah A.; Luster, Mary H.; Hering, Sandra L.; Bay, R. Curtis
Abstract: Purpose: To evaluate content validity and interrater reliability for acuity tools developed for the antepartum and neonatal intensive care unit (NICU) patient population. Study Design and Methods: Antepartum and NICU acuity tools were developed to better evaluate nurse staffing assignment equity and patient needs. Following several iterations with staff nurses and nurse leaders, content validity of the acuity tools was established via a panel of experts in each substantive area using the Content Validity Index. The final tools were then evaluated for interrater reliability using Intraclass Correlation. Results: Content validity for the Antepartum Acuity Tool was S-CVI/Ave = 0.87 and for the NICU Acuity Tool was S-CVI/Ave = 0.98. Interrater Reliability for the Antepartum Acuity tool was ICC = 0.88, and the NICU Acuity Tool was ICC = 0.95. Clinical Implications: These tools have established content validity and interrater reliability and are appropriate for use in the antepartum and NICU settings to determine patient acuity and promote appropriate nurse-to-patient assignments. Abstract : Acuity tools for the antepartum unit and neonatal intensive care unit were developed by a group of expert nurses. Content validity and interrater reliability were established. The tools can be used to identify patient care needs, make appropriate nurse-to-patient assignments, and support safe, high-quality maternity and neonatal nursing care.